2020
DOI: 10.3390/nano10091851
|View full text |Cite
|
Sign up to set email alerts
|

Synchrotron Characterization of Hexagonal and Cubic Lipidic Phases Loaded with Azolate/Phosphane Gold(I) Compounds: A New Approach to the Uploading of Gold(I)-Based Drugs

Abstract: Gold(I) phosphane compounds have recently attracted a renewed interest as potential new protagonists in cancer therapy. A class of phosphane gold(I) complexes containing azolate ligands has been successfully tested against several cancer cell lines and, in particular, against basal-like breast (BLB) cancer, a form characterized by strongly severe diagnosis and short life lapse after classic chemotherapy. Even though the anticancer activity of gold(I) phosphane compounds is thoroughly ascertained, no study has … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…Galassi and co-workers recently reported the encapsulation of (4,5-dichloroimidazolyl-1H-1yl) (triphenylphosphine)gold(I) (C-I, Figure 22a) and (4,5 dicyanoimidazolyl-1H-1yl) (triphenylphosphine)gold(I) (C-II, Figure 22a), in lyotropic liquid crystalline lipid NPs (P16) composed of three different building blocks (Figure 22b): Monoolein (GMO), phytantriol (PHYT) and dioleoyl phosphatidylethanolamine (DOPE). [280] C-I and C-II were successfully encapsulated in P16 formulations, as evidenced by the changes in the mesophase lattice parameters obtained from X-ray diffraction experiments, and by the spectral changes in the UV/Vis spectra of the gold complexes after loading, respectively. Since gold-phosphine complexes suffer from prompt ligand substitution reactions, their encapsulation is expected to enhance the stability and improve their therapeutic properties, [281][282][283] future work on in vitro and in vivo characterization of these types of nano-formulations will be of great interest.…”
Section: Particle Formulations Based On Non-covalent Loading Strategi...mentioning
confidence: 98%
See 1 more Smart Citation
“…Galassi and co-workers recently reported the encapsulation of (4,5-dichloroimidazolyl-1H-1yl) (triphenylphosphine)gold(I) (C-I, Figure 22a) and (4,5 dicyanoimidazolyl-1H-1yl) (triphenylphosphine)gold(I) (C-II, Figure 22a), in lyotropic liquid crystalline lipid NPs (P16) composed of three different building blocks (Figure 22b): Monoolein (GMO), phytantriol (PHYT) and dioleoyl phosphatidylethanolamine (DOPE). [280] C-I and C-II were successfully encapsulated in P16 formulations, as evidenced by the changes in the mesophase lattice parameters obtained from X-ray diffraction experiments, and by the spectral changes in the UV/Vis spectra of the gold complexes after loading, respectively. Since gold-phosphine complexes suffer from prompt ligand substitution reactions, their encapsulation is expected to enhance the stability and improve their therapeutic properties, [281][282][283] future work on in vitro and in vivo characterization of these types of nano-formulations will be of great interest.…”
Section: Particle Formulations Based On Non-covalent Loading Strategi...mentioning
confidence: 98%
“…Galassi and co‐workers recently reported the encapsulation of (4,5‐dichloroimidazolyl‐1H‐1yl) (triphenylphosphine)gold(I) ( C‐I , Figure 22a) and (4,5 dicyanoimidazolyl‐1H‐1yl) (triphenylphosphine)gold(I) ( C‐II , Figure 22a), in lyotropic liquid crystalline lipid NPs ( P16 ) composed of three different building blocks (Figure 22b): Monoolein (GMO), phytantriol (PHYT) and dioleoyl phosphatidylethanolamine (DOPE) [280] . C‐I and C‐II were successfully encapsulated in P16 formulations, as evidenced by the changes in the mesophase lattice parameters obtained from X‐ray diffraction experiments, and by the spectral changes in the UV/Vis spectra of the gold complexes after loading, respectively.…”
Section: Delivery Of Gold Chemotherapeutics Based On Micro‐ and Nanoc...mentioning
confidence: 99%
“…42,43 In Cu 6 -2 and Cu 6 -3 NCs, distinct vibrational bands around 1100 cm −1 were attributed to the C-P asymmetric stretching vibration. 44 The above results suggest that when phosphine ligands are coordinated to copper, the ligand backbone structures underwent no apparent changes.…”
Section: Resultsmentioning
confidence: 84%
“…Lyotropic liquid crystalline (LLC) mesophases, particularly cubic and hexagonal ones, have been extensively studied as vehicles for molecules of different size and polarity such as small drugs, vitamins, peptides, proteins, and nucleic acids. In fact, encapsulation permits the control of the release of the enclosed molecule in space and time, thus possibly allowing targeted therapies, and represents an efficient strategy for biomolecule stabilization. Recently, we reported the use of phytantriol (PHYT) or monoolein cubosomes for the loading and delivery of vitamin B12 and different anticancer compounds, namely, the commonly used 5-fluorouracil, , the plant extract isofuranodiene, and phosphane gold­(I) compounds, and demonstrated that encapsulation increased the drug stability and hence its anticancer activity. Bicontinuous cubic phases consist of a single, continuous bilayer draped over an infinite periodic minimal surface, subdividing space into two interpenetrating but unconnected water networks .…”
Section: Introductionmentioning
confidence: 99%